Tetramethylpyrazine alleviates cerebral ischemia-reperfusion injury via NRF2/HO-1/GPX4-mediated ferroptosis inhibition - Hengpei Gong; Yinjun Lu; Lingfeng Wang; Xueyuan Gong; Jingfang Zhao; Zhenxin Li (Tissue and Cell, 2027)

Mechanisms underlying the impacts of antibiotics on soil microbes and enzyme activities in urban green spaces - Jingfang Li; Liang Chen; Zhibin Jia; Fawen Li (Applied Soil Ecology, 2026)

In situ real-time continuous monitoring of soil carbonate ions using a portable CuO–Cu2O-based electrochemical sensor - Yuying Bao; Jingfang Ji; Jiyu Chen; Kaiquan Li; Pan Liu; Jingmin Ge; Ronghan Wei; Xiaodong Lei; Jingwei Zhang (Analytica Chimica Acta, 2026)

Clay mineral evidence for sediment provenance and the evolution of the East Asian Winter Monsoon in the central Philippine Sea over the last 4.38 Ma - Jun Sun; Fei Guo; Huaichun Wu; Wei Huang; Jian Liu; Kai Lu; Jingfang Lu; Shuang Sun; Meinan Shi; Boya Li; Liwei Liu; Xiaoke Qiang (Global and Planetary Change, 2026)

Research Progress on the Molecular Regulatory Mechanisms of Non-organellar Localization of PPR Proteins - Xuezhong Li; Junyi Yan; Lingyan Zhou; Ying He; Jingfang Dong; Chuxiong Zhuang (Plant Molecular Biology Reporter, 2026)

An adaptive hybrid modeling approach integrating elastic net and Kriging for activated sludge treatment - Yaohui Li; Zebin Zhang; Zhifeng Yin; Jingfang Shen; Wenwei Liu (Environmental Research, 2026)

Lanthanide-polyoxometalate-based anti-swelling luminescent conductive organohydrogel for information encryption and underwater sensing - Xinyu Lu; Jingfang Li; Min Gao; Sicong Zhao; Guangming Li (Chemical Engineering Journal, 2026)

Holistic evolution of the Bohai Sea complex system: Insights from interacting drivers - Han Huang; Tao Zou; Teng Liu; Hongyu Wang; Zhixuan Wang; Ningning Tao; Yanfang Li; Hao Fan; Fei Xie; Weidong Zhai; Guizhi Wang; Yongwen Zhang; et al. (Marine Environmental Research, 2026)

Multifunctional conductive luminescent hydrogel with low-temperature enhanced mechanical properties: Applications in sensing, gas detection, and information encryption - Min Gao; Jingfang Li; Yumei Hua; Sicong Zhao; Guangming Li (Chemical Engineering Journal, 2026)

MnSO₄-synergized oyster shell powder outperforms rice straw in mediating dual abiotic and microbial pathways for paddy cd remediation - Guofei Liu; Jingfang Li; Weixiong Jiao; Ye Li; Xiaoyuan Yin; Dasong Lin (Chemical Engineering Journal, 2026)

Advancing carbon neutrality through innovative soil remediation strategies: Co-application of materials and MnSO4 for cadmium-contaminated paddy soils - Guofei Liu; Yanru Zhang; Zhehan Li; Weixiong Jiao; Jingfang Li; Xiaoyuan Yin; Dasong Lin (Journal of Environmental Chemical Engineering, 2025)

Multidimensional quality assessment (nutrients and aroma) of dried kiwifruit: Unveiling the advantages of radio frequency-vacuum drying - Jingfang Ao; Shaojin Wang; Xingshu Li; Chung Lim Law; Long Chen (Food Chemistry, 2025)

Effects of woody plant roots on migration of ciprofloxacin and tylosin in soil - Jingfang Li; Huiting Ma; H.U. Xiaoming; Liang Chen; Paul H. Fallgren (Journal of Contaminant Hydrology, 2025)

Dendritic-honeycomb porous polyoxometalate/MXene films for supercapacitor applications - Xinzheng Li; Yingyi Ma; Xinran Li; Yu Si; Kexin Liu; Shiyun Wang; Zhihao Zhu; Jingfang Li (Chemical Engineering Journal, 2025)

Prevalence of Avian Influenza Viruses and Biomolecular Analysis of H9N2 Subtype in Live Poultry Markets from 2021 to 2023 in Changsha, China - Xian Zhang; Yutong Wang; Xiaoyu Li; Zheng Huang; Huiyuan Fu; Ruiqing Pei; Caiying Zhu; Yu Di; Shan Chen; Jingfang Chen; Mingzhong Xu; Xuewen Yang; et al. (Food and Environmental Virology, 2025)

The roles of flaxseed gum and its oligosaccharides as stabilizers in zein nanoparticles for apigenin delivery: Stability, antioxidant activity, bioavailability, molecular simulations - Yufei Liu; Ziliang Li; Shuaijun Lu; Shang Gao; Mengting Xu; Ze Yuan; Yue Li; Yiqiao Gao; Jingfang Shangguan; Xia Xiang (Food Chemistry, 2025)

Transcriptome sequence reveal the roles of MaGME777 and MabHLH770 in drought tolerance in Musa acuminata - Yuchen Wei; Jingfang Shi; Xueyi Xie; Feng Zhang; Huizhen Dong; Yaoyao Li; Fangcheng Bi; Xiaosan Huang; Tongxin Dou (Plant Science, 2025)

Comprehensive study of heavy precipitation events over land using climate network analysis - Kaiwen Li; Ming Wang; Kai Liu; Jingfang Fan (Journal of Hydrology, 2025)

A global optimization method based on fuzzy clustering Kriging for aerobic wastewater treatment - Yaohui Li; Shuting Wang; Yizhong Wu; Zebin Zhang; Jingfang Shen (Journal of Environmental Management, 2025)

Synchronization patterns of extreme rainfall events in Southwest China - Panjie Qiao; Xiaojuan Wang; Wenqi Liu; Shuai Li; Yongwen Zhang; Guolin Feng; Jingfang Fan (Climatic Change, 2025)

Adding non-crop plants enhances parasitoid fitness on potato plants, but not pest densities - Yusha Wang; Yongping Zhou; Ruwen Li; Ambreen Masqsood; Hongsong Chen; Zhenqiang Qin; Jingfang Yang; Jiali Zhang; Lin Jing; Huihua Tan; Zhongshi Zhou (Crop Protection, 2025)

Interface engineering of Platinum–Copper alloy/titanium dioxide for enhanced photocatalytic carbon dioxide reduction - Xin Wang; Wei Tan; Bo Peng; Shangcong Sun; Xue Li; Kaiqiang Wang; Jiawei Ji; Haohong Liao; Jingfang Sun; Qing Tong; Haiqin Wan; Lin Dong (Environmental Research, 2024)

High Frequency of Autoantibodies in COVID-19 Patients with Central Nervous System Complications: a Multicenter Observational Study - Jingfang Lin; Dong Zheng; Decai Tian; Pei Zheng; Hongya Zhang; Chuo Li; Chunliang Lei; Fudong Shi; Honghao Wang (Molecular Neurobiology, 2024)

Multi-stimuli-responsive conductive and luminescent hydrogels for wearable sensors and information encryption transmission - Min Gao; Jingfang Li; Sicong Zhao; Guangming Li (Chemical Engineering Journal, 2024)

Co-pyrolytic drivers and volatiles of 3D printing waste and textile dyeing sludge and their multi-objective optimization - Ziting Lin; Xiaoming Li; Jingfang Mou; Fatih Evrendilek; Jingyong Liu; Jiayu Liang; Sen Lin; Haiming Cai; Yao He; Guanzheng Zhuang; Chunxiao Yang (Chemical Engineering Journal, 2024)

Co-occurrence patterns of gut microbiome, antibiotic resistome and the perturbation of dietary uptake in captive giant pandas - Yuhao Fu; Feiran Jia; Jingfang Su; Xinyao Xu; Yuqin Zhang; Xiangzhen Li; Xin Jiang; Andreas Schäffer; Marko Virta; James M. Tiedje; Fang Wang (Journal of Hazardous Materials, 2024)

Enhanced AGS by granular activated carbon loaded with nano iron when treating low strength and low COD/TN ratio municipal wastewater: Microbial metabolism, electron transfer and enhancement mechanism - Lei Peng; Haibo Li; Jianbo Guo; Jingfang Lu; Yanan Hou; Yi Han; Daohong Zhang; Yuanyuan Song; Jianhai Zhao (Journal of Environmental Chemical Engineering, 2024)

Preparation of Anderson-type CoMo6-2NH2@ECOF for highly active catalysis on aerobic oxidative desulfurization of fuel under O2 - Xue Lu; Jingfang Li; Liye Liang; Guangming Li (Fuel, 2024)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

Substrate specificity of polyphenol oxidase and its selectivity towards polyphenols: Unlocking the browning mechanism of fresh lotus root (Nelumbo nucifera Gaertn.) - Jingfang Li; Ze-yuan Deng; Huanhuan Dong; Rong Tsao; Xiaoru Liu (Food Chemistry, 2023)

A pervasive phosphorylation cascade modulation of plant transcription factors in response to abiotic stress - Wang Baoxiang; Sun Zhiguang; Liu Yan; Xu Bo; Li Jingfang; Chi Ming; Xing Yungao; Yang Bo; Li Jian; Liu Jinbo; Chen Tingmu; Fang Zhaowei; et al. (Planta, 2023)

PBX1-promoted SFRP4 transcription inhibits cell proliferation and epithelial-mesenchymal transition in endometrial carcinoma - Liwen Guo; Huihua Chen; Jinguo Chen; Chen Gao; Xianguo Fu; Sujuan Zhou; Wenjuan Wu; Taoping Li; Jingfang Lin; Tailai Yang; Zichun Chen; Luoyuan Cao (Tissue and Cell, 2023)

Distribution of gold derived from hydrothermal fluids on the modern seafloor and its impact on the gold budget of seawater - Wei Huang; Jin Liang; Jingfang Lu; Fanghui Hou; Panfeng Li; Ruyong Cui (Frontiers in Marine Science, 2023)
The modern seafloor hydrothermal system plays a significant role in the cycling of energy and mass between the internal and external layers of the oceanic crust and upper mantle. It continues to supply hydrothermal fluids containing three to five orders of magnitude more gold into the ocean than the amount typically present in deep seawater. It has a considerable impact on the distribution and budget of gold with respect to the large geological inventory of the ocean along with other input sources such as river water. The large amount of various types of data compiled for this study reveals that only about 0.3% of the annual hydrothermal flux of gold (2618.3 kg/a) injected into the overlying seawater column as a dissolved phase is eventually trapped in sulfide deposits near vent sites on the seafloor, while about 0.8% is trapped in metalliferous sediments that fall out from the distal nonbuoyant plume. The remaining ~98.9% of gold is delivered into the depths of the global open ocean. The global budget of gold in seawater (about 1.4 × 10 7 kg), the annual flux of hydrothermal fluids at the seafloor (about 2.6 × 10 3 kg/a), the amount delivered by river water (about 7.2 × 10 4 kg/a), and significant estuarine removal (15%) allows us to estimate the residence time of gold in the modern ocean to be about 220 years. This value is 70% shorter than that (~1000 years) reported previously. In the future, the use of appropriate artificial means to achieve more efficient precipitation of gold from the hydrothermal system at the seafloor could increase the level of enrichment of gold to obtain gold-rich hydrothermal deposits, yielding greater economic benefits.

Effects of nitrogen and phosphorus supply levels and ratios on soil microbial diversity-ecosystem multifunctionality relationships in a coastal nontidal wetland - Kai Sun; Jingfang Cai; Xiaoling Liu; Lijuan Yang; Hongli Li; Guangmei Wang; Xingliang Xu; Feihai Yu (Science of The Total Environment, 2023)

Integrated volatilomic profiles and chemometrics provide new insights into the spatial distribution and aroma differences of volatile compounds in seven Toona sinensis cultivars - Cheng Wang; Chendan Fu; Yanfang Li; Yilan Zhang; Beibei Zhang; Jingfang Zhang (Food Chemistry, 2023)

Integrated transcriptomic and volatilomic profiles to explore the potential mechanism of aroma formation in Toona sinensis - Cheng Wang; Beibei Zhang; Yanfang Li; Jing Hou; Chendan Fu; Zihui Wang; Jingfang Zhang (Food Research International, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

The inhibitory mechanism of pentacyclic triterpenoid acids on pancreatic lipase and cholesterol esterase - Heyu Shen; Jun Wang; Jingfang Ao; Lixia Ye; Yubing Shi; Yujie Liu; Mengyang Li; Anwei Luo (Food Bioscience, 2023)

The neglected potential source of microplastics from daily necessities: A study on protective mobile phone cases - Qilu Li; Meng Yuan; Yuan Chen; Xinjie Jin; Jingfang Shangguan; Jinle Cui; Shixiang Chang; Mengran Guo; Yan Wang (Journal of Hazardous Materials, 2023)

The impact of three related emission industries on regional atmospheric chlorinated paraffins pollution - Qilu Li; Shanshan Jiang; Yajing Li; Jingjing Su; Jingfang Shangguan; Mengdi Zhan; Yan Wang; Xianfa Su; Jun Li; Gan Zhang (Environmental Pollution, 2023)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Estimation of Avian Influenza Viruses in Water Environments of Live Poultry Markets in Changsha, China, 2014 to 2018 - Xiaoyu Li; Rusheng Zhang; Zheng Huang; Dong Yao; Lei Luo; Jingfang Chen; Wen Ye; Lingzhi Li; Shan Xiao; Xiaolei Liu; Xinhua Ou; Biancheng Sun; et al. (Food and Environmental Virology, 2022)

The crosstalk between the Notch, Wnt, and SHH signaling pathways in regulating the proliferation and regeneration of sensory progenitor cells in the mouse cochlea - Jingfang Wu; Wen Li; Luo Guo; Liping Zhao; Shan Sun; Huawei Li (Cell and Tissue Research, 2021)
Sensory hair cells (HCs) are highly susceptible to damage by noise, ototoxic drugs, and aging. Although HCs cannot be spontaneously regenerated in adult mammals, previous studies have shown that signaling pathways are involved in HC regeneration in the damaged mouse cochlea. Here, we used a Notch antagonist (DAPT), a Wnt agonist (QS11), and recombinant Sonic hedgehog (SHH) protein to investigate their concerted actions underlying HC regeneration in the mouse cochlea after neomycin-induced damage both in vivo and in vitro. With DAPT, the numbers of HCs increased, and supporting cell (SC) proliferation was seen in both the intact and damaged cochlear sensory epithelia, while these numbers were unchanged in the presence of QS11. When simultaneously treated with DAPT and QS11, the number of HCs increased dramatically, and much greater SC proliferation was seen in the cochlear epithelium. In transgenic mice with both Notch1 conditional knockout and β-catenin over-expression, cochlear SC proliferation and HC regeneration were more obvious than in either Notch1 knockout or β-catenin over-expressing mice separately. When cochleae were treated with DAPT, QS11, and SHH together, SC proliferation was even greater, and this proliferation was seen in both the HC region and the greater epithelial ridge. High-throughput RNA sequencing was used to identify the differentially expressed genes between all groups, and the results showed that the SHH and Wnt signaling pathways are involved in SC proliferation. Our study suggests that co-regulation of the Notch, Wnt, and SHH signaling pathways promotes extensive cell proliferation and regeneration in the mouse cochlea.

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

Evolution of the novel coronavirus from the ongoing Wuhan outbreak and modeling of its spike protein for risk of human transmission - Xintian Xu; Ping Chen; Jingfang Wang; Jiannan Feng; Hui Zhou; Xuan Li; Wu Zhong; Pei Hao (Science China Life Sciences, 2020)

Effects of Soil Properties and Land Use Types on the Bioaccessibility of Cd, Pb, Cr, and Cu in Dongguan City, China - Haoqi Tian; Yuzhe Wang; Jingfang Xie; Hua Li; Yuen Zhu (Bulletin of Environmental Contamination and Toxicology, 2020)

Hybrids of oxoisoaporphine–tetrahydroisoquinoline: novel multi-target inhibitors of inflammation and amyloid-β aggregation in Alzheimer’s disease - Yusi Chen; Chunlin Su; Li Wang; Jingfang Qin; Shenqi Wei; Huang Tang (Molecular Diversity, 2019)

OsNDUFA9 encoding a mitochondrial complex I subunit is essential for embryo development and starch synthesis in rice - Tingting Hu; Yunlu Tian; Jianping Zhu; Yunlong Wang; Ruonan Jing; Jie Lei; Yinglun Sun; Yanfang Yu; Jingfang Li; Xiaoli Chen; Xiaopin Zhu; Yuanyuan Hao; et al. (Plant Cell Reports, 2018)

Transcriptomic analysis reveals the effect of the exopolysaccharide of Psychrobacter sp. B-3 on gene expression in RAW264.7 macrophage cells - Pingping Zhang; Jiang Li; Leiye Yu; Jingfang Wei; Tong Xu; Guojie Sun (Acta Oceanologica Sinica, 2018)

Characterization and genomic analyses of Aeromonas hydrophila phages AhSzq-1 and AhSzw-1, isolates representing new species within the T5virus genus - Shengjian Yuan; Ling Chen; Quan Liu; Yan Zhou; Jingfang Yang; Deng Deng; Hongping Li; Yingfei Ma (Archives of Virology, 2018)

Purification and antibacterial mechanism of fish-borne bacteriocin and its application in shrimp (Penaeus vannamei) for inhibiting Vibrio parahaemolyticus - Xinran Lv; Jingfang Du; Yu Jie; Bolin Zhang; Fengling Bai; Hongfei Zhao; Jianrong Li (World Journal of Microbiology and Biotechnology, 2017)

A bFGF Antagonist Peptide with Anti-angiogenesis Properties in Non-small Cell Lung Cancer Cells - Ruixue Wang; Wu Luo; Xiangfeng Zeng; Jingfang Di; Yonglin Yu; Chuan Wang; Wenhui Wang; Xilei Chen; Dan He; Tao Li; Xiaoping Wu (International Journal of Peptide Research and Therapeutics, 2013)

Functional evaluation of four putative DNA-binding regions in Thermoanaerobacter tengcongensis reverse gyrase - Jie Li; Jingfang Liu; Jian Zhou; Hua Xiang (Extremophiles, 2011)

Steroidal saponins from the rhizomes of Polygonatum odoratum - Dongmei Wang; Dengwu Li; Wei Zhu; Jingfang Zhang; Pai Peng (Natural Product Research, 2009)

Effects of Sulfur Dioxide on the Expressions of EGF, EGFR, and COX-2 in Airway of Asthmatic Rats - Ruijin Li; Ziqiang Meng; Jingfang Xie (Archives of Environmental Contamination and Toxicology, 2008)

Complete sequence and molecular characterization of pNB101, a rolling-circle replicating plasmid from the haloalkaliphilic archaeon Natronobacterium sp. strain AS7091 - Meixian Zhou; Hua Xiang; Chaomin Sun; Yun Li; Jingfang Liu; Huarong Tan (Extremophiles, 2004)